Federated States of Micronesia : Technical Assistance Report-Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2021)
The International Monetary Fund's (IMF's) Statistics Department (STA) provided technical assistance (TA) on financial soundness indicators (FSI) to the Federated States of Micronesia Banking Board (FSMBB) during November 2-13, 2020. The TA mission took place in response to a request from the authorities, with the support of the IMF's Asia and Pacific Department (APD). The mission was conducted remotely via video conferences due to the COVID-19 pandemic and travel restrictions. The mission worked with the staff of the FSMBB on the development of FSIs that are in line with the IMF's 2019 FSI Guide.1 The main objectives of the mission were to: (i) review the source data, institutional coverage and accounting and regulatory frameworks supporting the compilation of FSIs; (ii) provide guidance for mapping source data for the banking sector to the FSI reporting templates FS2 and FSD as well as areas for improvement in the metadata; (iii) agree with the FSMBB the timeline to begin regular reporting of the FSIs for deposit-takers to STA, conditional on the availability and completeness of the source data; and (iv) agree on the timeliness of data reporting.